The girls in the back room : looking at the lesbian bar - Hankin, Kelly (University of Minnesota Press, 2002)
The lesbian bar has long been seen as a mysterious place, steeped in mythologies of clandestine meetings and sexuality that is alluring because it is wayward and sinful. Kelly Hankin focuses on the lesbian bar, looking at how it is portrayed in such films as Foxy Brown, The Killing of Sister George, Basic Instinct, Bound, and Chasing Amy; in television series like The Simpsons, Xena: Warrior Princess, Roseanne, Ellen, and Sex and the City; and in independent, lesbian-produced documentaries. The Girls in the Back Room provides an engaging historical and theoretical analysis of the visual lesbia.